Shifting confidence in homeownership: The great recession - Anat Bracha; Julian C. Jamison (Federal Reserve Bank of Boston, 2012)
The authors study the responses to several questions related to real estate that were added to the Michigan Survey of Consumers in July and August 2011. In particular, they asked about attitudes toward renting versus buying a home, about commuting, and about how much to spend on a mortgage. By matching the results to data (at the ZIP-code level) about relative house price declines during the recent crisis, they can study the relationship between the U.S. housing crash and the attitudes of individual consumers. They find that younger respondents are relatively less confident about homeownership after larger price declines, while older respondents are relatively more confident. In both cases, this is observed only for those with direct experience of loss (via themselves or someone close) during the crash. They find no effect on attitudes towards commuting, and they find that people who live in the high-decline areas believe it is appropriate to spend more on a mortgage.
Keywords: R21; E32; D12; D03; D83; 330; Wohneigentum; Miete; Hypothek; Private Verschuldung; Immobilienfinanzierung; Immobilienpreis; Relativer Preis; Michigan; USA